Contaminação ambiental por efluentes e micropoluentes: efeitos toxicológicos sobre peixes da espécie Cyprinus carpio - Dezorzi, Gabriela Dias (2021)
The absence of treatment or the ineffective treatment of effluents is one of the biggest sanitary problems in Brazil, since several potentially dangerous substances can be transported through them, being constantly discharged into the environment. In this sense, this study aimed to determine the influence of the final disposal of domestic effluents and micropollutants on the contamination of Sanga Lagoão do Ouro at UFSM, using Cyprinus carpio. For this, on April 7 (autumn) and July 20 (winter) 2021, surface water samples were collected from the water resource that receives effluent (P1, P2, P3) and from the effluent points (P4, P5, P6, P7). The physicochemical and microbiological characteristics were determined, as well as the metal contents in the surface water and effluent samples, and the concentrations of drugs and pesticides in the surface water samples. Subsequently, Cyprinus carpio was exposed to samples from the first surface water collection and after 3, 7 and 10 days of exposure in the laboratory, biochemical and toxicological parameters were evaluated through the activity of catalase (CAT) and glutathione S-transferase (GST ) in liver and acetylcholinesterase (AChE) activity in brain and muscle. Moreover, the potential oxidative damage was analyzed, with the determination of the levels of lipid peroxidation and protein carbonylation in intestine, gills, liver, brain and muscle. Non-conformity of effluent discharge was evidenced in accordance with CONAMA Resolution No. 357/2005, as well as the low quality of the water resource (Class 4). The presence of metals in the effluent and surface water indicate that these compounds are introduced into the aquatic environment due to human action. Eleven pesticides and also eleven pharmaceuticals were detected in surface water samples. Pesticides are related to the existence of irrigated rice, soy, corn and wheat crops in nearby areas, while pharmaceuticals are associated with the inadequate disposal of medicines and the release of domestic and hospital effluents. The contaminants detected in this study changed the biochemical parameters of fish, causing stress and oxidative damage evidenced by the activation of the antioxidant defense system and the occurrence of lipid peroxidation and protein carbonyl formation in all tissues analyzed, with the greatest damage occurring in the exposed organisms to samples collected in P2 (muscle, intestine, gills and liver) and P3 (brain, muscle and gills). With these results, it can be concluded that the release of effluents into the soil and subsequent runoff to the water resource has contributed to its contamination and toxicity. Thus, the use of Cyprinus carpio as a bioindicator proved to be efficient, indicating that measures for the improvement of UFSM's liquid effluent treatment and disposal systems should be pursued, aiming to protect the aquatic environment and human health.